Probelam Kepala Sekolah dalam Meningkatka Manajeman Pendidikan di Sekolah Dasar - Muhammad, Suratni (Jurnal Ilmiah Wahana Pendidikan, 2023)
The aim of this research is to find out and provide solutions to school principals' problems in aspects of educational management in elementary schools. This research uses a qualitative descriptive research method with data collection used is observation, in-depth interviews, documentation. The data analysis technique uses data reduction by selecting the main things and focusing on the problems that exist in the institution, so that it can provide a more focused and up-to-date picture. The results of the research show that there are problems with the human resources of educators and education staff, public trust is still not high in institutions, the performance of educators and education staff still requires stimulus and still has honorary status and the local education service is still lacking in monitoring existing developments. in private school institutions.